We only find them when they're dead - Ewing, Al (BOOM! Studios, 2021)
"Captain Malik and the crew of his spaceship are in search of the only resources that matter - and can only be found by harvesting the giant corpses of alien gods that are found on the edge of human space..and now they see an opportunity to finally break free from this system: by being the first to find a living god. THE GODS ARE ALWAYS BEAUTIFUL... ...AND THE GODS ARE ALWAYS DEAD. Captain Malik and the crew of the spaceship the Vihaan II are in search of the only resources that matter - and can only be found by harvesting the giant corpses of alien gods that are found on the edge of human space. While other autopsy ships and explorers race to salvage the meat, minerals, and metals that sustain the human race, Malik sees an opportunity to finally break free from this system: by being the first to find a living god. But Malik's obsession with the gods will push his crew into the darkest reaches of space, bringing them face to face with a threat unlike anything they ever imagined, unless the rogue agent on their trail can stop them first... Superstars Al Ewing and Simone Di Meo present a new sci-fi epic about the search for meaning and the hard choices we make to find it, no matter the cost to the world - or universe - around us."--Publisher's website.